Early Detection of Critical Congenital Heart Disease Through Pulse Oximetry Screening In Resource-Limited Settings - M Bambang Edi Susyanto; Nadya Arafuri; Dyah Ayu Shinta Lesmanawati (International Journal of Health and Pharmaceutical (IJHP), 2025)
Critical congenital heart disease (CCHD) is a major cause of neonatal mortality. Early detection using pulse oximetry (SpO₂) within 24–48 hours of life improves survival by identifying hypoxemia before clinical deterioration. A feasibility study in Yogyakarta, Indonesia, screened 1,452 newborns and detected eight CCHD cases (~6 per 1,000 live births), confirming its value in limited-resource settings. A full-term female neonate delivered by elective cesarean section had an initial SpO₂ of 96% but developed cyanosis within 24 hours, with saturation dropping to 90%. Abnormal SpO₂ results led to referral, and echocardiography confirmed critical pulmonary stenosis with PDA and PFO. Balloon valvuloplasty was performed successfully, normalizing oxygen levels. Pulse oximetry screening shows moderate sensitivity (76–83%) and high specificity (~99.9%) for detecting CCHD. Despite logistical and training challenges, it remains feasible and cost-effective in low- and middle-income settings. Integrating SpO₂ screening into routine newborn assessment, supported by national policy and staff training, can enhance early diagnosis and reduce neonatal deaths related to undetected CCHD.